Implikasi Perang Dagang AS-China Terhadap Stabilitas Ekonomi Indonesia - Pandiangan, Tawarika M.; Sihite, Samuel; Simbolon, Alissa Putri; Manik, Vinolya Lidevia Br; Tamba, Ida Nurjana; Simanjuntak, Rian Todo Redyson (Indo-MathEdu Intellectuals Journal, 2023)
Five years since the start of the trade war, hostilities between the United States (U.S.) have shown no sign of an end. Between the two countries, the US President donal trump has issued a high-price policy on China's imports and is blocking the supply of key technologies. In turn, China has helped impose high rates on U.S. exports and have enabled unreliable listings of tentacles. The aim of the study is to analyze the conflict between the two largest economic countries and know the impact on Indonesia's economic stability. The study employed qualitative research methods with literature studies. The results suggest that both countries feel unjust upon bilateral trade practices. The controversy comes because of ambitions from both countries pursuing the highest economic rankings, racing to correct trade deficits from each country